POLA ALIRAN UDARA PADA TURBIN ANGIN SAVONIUS HELIKS DENGAN VARIASI JUMLAH SUDU MENGGUNAKAN METODE CFD - Muhammad Harist Mishbahuddin; Taufik Wisnu Saputra; Danar S. Wijayanto (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2024)
The availability of fossil resources is decreasing, cause government and private sectors to race in developing renewable energy. One solution is to create Wind Power Plants to meet energy demands. The Savonius turbine, also known VAWT, this great potential to meet small-scale energy needs. Savonius turbines have lower performance compared to other types. This performance needs to be enhanced through design modifications, such as varying the number of blades. This research purpose is to analyze effect number of blades on performance of helical Savonius turbines. This research focuses on airflow patterns with varying blade numbers in helical Savonius turbines. These turbines numerically studied using Computational Fluid Dynamics (CFD) approach with ANSYS Fluent. Each variation of blade numbers will simulate at wind speeds between 1 to 5 m/s. Numerical testing results will provide visualizations in form contour and vector within pressure or velocity scope for each variation. Based on visualization of numerical testing results, found that number of blades affects flow patterns. Increasing the number of blades increases turbulence flow. Pressure on convex surface also increases with the addition of blades. These two airflow phenomena reduce turbine performance, so two blades produce most optimal performance due to minimal resistance they experience.